A rare case of CD5 positive extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) arising in a female breast after surgical excision of an inflammatory pseudotumor - Branca, Giovanni; Ieni, Antonio; Irato, Eleonora; La Malfa, Giuseppe; Lorenzini, Cesare; Guccione, Fabio; Palmeri, Renato (European Journal of Oncology and Environmental Health, 2016)
Primary lymphoma of the breast is extremely rare accounting for 0.04-0.5% of all breast malignancies. Up to 50% (56-84%) are diffuse large B-cell lymphomas, and indolent histological types such as extranodal marginal zone lymphomas of mucosa-associated lymphoid tissue (MALT lymphoma) occur rarely with a reported incidence variable between 0 and 64%, corresponding to less than 0.5% of overall malignant neoplasms of the breast. A 38-year-old Caucasian woman was admitted to the surgery unit nine months after the excision of a pre-existing inflammatory pseudotumor of the breast because mammography investigation revealed asymmetrical, ill-defined parenchymal accumulation located in the right axillary prolongation. The final diagnosis was obtained after surgical excision and pathological evaluation of the mass. Histological features and the immunohistochemical profile, characterized by positive expression of the lymphoid tumor cells for CD20, BCL-2, and CD5 together with lambda light chain monoclonality and negativity for Cyclin D1, supported the diagnosis of a CD5 positive extranodal marginal zone lymphoma of MALT.